Pomiar efektywności działania banków komercyjnych - Korzeb, Zbigniew (The Efficiency Measurement of Commercial Banks, 2005)
Over the past two decades, Data Envelopment Analysis (DEA) has emerged as an important tool in the field of efficiency measurement of commercial banks. Data envelopment analysis is a linear programming based technique for measuring the relative performance of organisational units where the presence of multiple inputs and outputs makes comparisons difficult. The use of DEA is demonstrated by evaluating the management of 48 banks in Poland in 2003.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 252-260